Posterior lamellar reconstruction: a comprehensive review of the literature. (2nd January 2019) - Fin, Alessandra; De Biasio, Fabrizio; Lanzetta, Paolo; Mura, Sebastiano; Tarantini, Anna; Parodi, Pier Camillo
ABSTRACT: The aim of the review is to describe the different techniques and materials available to reconstruct the tarsoconjunctival layer of the eyelid; to analyze their indications, advantages, and disadvantages. We searched the Cochrane, PubMed, and Ovid MEDLINE databases for English articles published between January 1990 and January 2017 using variations of the following key words: "posterior lamella, " "eyelid reconstruction, " "tarsoconjunctival, " "flap, " and "graft." Two reviewers checked the abstracts of the articles found to eliminate redundant or not relevant articles. The references of the identified articles were screened manually to include relevant works not found through the initial search. The search identified 174 articles. Only a few articles with a therapeutic level of evidence were found. Techniques for the posterior lamellar reconstruction can be categorized as local, regional, and distant flaps; tarsoconjunctival, heterotopic, homologous, and heterologous grafts. Several techniques and variations on the techniques exist to reconstruct the posterior lamella, and, for similar indications, there's no evidence of the primacy of one over the other. Defect size and location as well as patient features must guide the oculoplastic surgeon's choice. The use of biomaterials can avoid possible complications of the donor site.